Efficient photoelectrochemical conversion of CO2 to ethylene and methanol using a Cu cathode and TiO2 nanoparticles synthesized in supercritical medium as photoanode. Issue 3 (June 2022) - Merino-Garcia, Ivan; Castro, Sergio; Irabien, Angel; Hernández, Ignacio; Rodríguez, Verónica; Camarillo, Rafael; Rincón, Jesusa; Albo, Jonathan
Abstract: The photoelectrochemical conversion of CO2 into valuable products represents an attractive method to decrease the external electrical bias required in electrochemical approaches. In this work, TiO2 nanoparticles with enhanced optical properties, large surface area, appropriate morphology, and superior crystallinity are synthesized in supercritical medium to manufacture light-responsive photoanodes. The photoelectrochemical CO2 reduction tests are carried out in continuous mode using a photoanode-driven filter-press cell illuminated with UV LED lights (100 mW cm -2 ), consisting on TiO2 nanoparticles synthesized in supercritical medium (3 mg cm -2 ) supported onto porous carbon paper as the photoanode, a Cu plate cathode, and 1 M KOH aqueous solution as the reaction medium. The main products obtained from CO2 are ethylene in the gas phase, together with methanol in the liquid phase. The results show that reaction performance is improved under UV irradiation towards ethylene ( r  = 147.4 μmol m −2 s −1 ; FE = 46.6%) and methanol ( r  = 4.72 μmol m −2 s −1 ; FE = 15.3%) in comparison with the system performance in the dark (ethylene: r  = 24.2 μmol m −2 s −1 and FE = 38.2%; methanol not detected), which can be mainly ascribed to the superior photocurrent densities reached that affect the selectivity of the reaction. Besides, the maximum solar-to-fuels values achieved for ethylene (5.4%) and methanol (1.9%) are markedly superior to those observed with illuminated TiO2 -P25 photoanodes under the same reactor configuration and experimental conditions (3.7% and 1%, respectively). Therefore, these results demonstrate the benefits of using TiO2 -based materials synthesized in supercritical medium for a more efficient continuous photoelectroreduction of CO2 to value-added products. Graphical Abstract: ga1